IMPLEMENTASI NILAI-NILAI KARAKTER LEADERSHIP MELALUI KEGIATAN TRAINING OF TRAINER FOR QUR’AN GENERATION (TOTQG) UNIT KREATIVITAS MAHASISWA JAM’IYYATUL QURRO’ WAL HUFFADZ UNIVERSITAS ISLAM MALANG - Azalia Fitriana Brigita; Abdul Jalil; Mutiara Sari Dewi (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
This study is aimed to describe the implementation of leadership character building and the result of it, through the activity Training Of Trainer For Qur’an Generation Student Creativity Unit Jam’iyyatul Qurro’ Wal Huffadz Islamic University of Malang. The approach of qualitative research is used in this study. Collecting data techniques used observation, interview, and documenting. The result of this study showed the implementation of leadership character in the activity with giving materials such as administration and commission, JQH education, leadership and organization materials. Furthermore, the committee also gave the problem solving activity and communal work. For the inauguration, the committee held the asseveration ceremonial as the closing activity. The outcome of this activity was the participants got new knowledge, became more responsible and also reliable in committing their duty.